Analisis Dan Pengembangan Sistem Informasi Penerimaan Mahasiswa Baru Berbasis Web Pada Pascasarjana Universitas Jambi - Andry Almustaqim; Herry Mulyono (Jurnal Manajemen Sistem Informasi, 2017)
Information system of admission new college student based web at Pascasarjana Universitas Jambi stillfound many weaknesses for instance. The aplplicants who did the process of registration and the won’tchange the data because the can’t login into the system, the form of registration only can printed once, soif lost hte applicants can’t print out anymore and should inform to the staff. Administrator and program ofstudy can’t monitored the listed of how many applicants who verified. Form this matter the researcherdeveloping of system with waterfall method for admission new college student at PascasarjanaUniversitas Jambi. It could beasier for the applicants to correcting of data and to print the form ofregistration, administrator and program of study can monitored the listed of how many applicants whoverified. The development of this system can solve all the problem so far